POTENSI LAHAN TANAMAN PISANG ABAKA (Musa textilis Nee) DI PT. VIOLA FIBER INTERNASIONAL DESA SILIAN KABUPATEN MINAHASA TENGGARA - Pertiwi Daeng Patompo; Jody M. Mawara; Berry R.V. Joseph (COCOS, 2018)
ABSTRACT            This research entitled "Potential of Abaka Banana Plant Land (Musa Textilis Nee) at PT. Viola Fiber International, Desa Silian, Kabupaten Minahasa Tenggara "aims to find out the suitability class of Abaka banana plantations and examine the potential for potential and actual land suitability of Abaka banana plants. This research was conducted in October - November 2017, in the Plantation area of PT. International Fiber Viola, Desa Silian, Kabupaten Minahasa Tenggara. The study area has a sloping topography with a height of 613 masl, using a survey method to obtain primary and secondary data. The results of the study show that the actual suitability of S2rcna is quite in accordance with the limiting factor for root media (rc), especially texture and nutrient availability (N, P, K). With the effort to improve management by adding organic matter, using mulch and fertilizing N (urea), P (TSP / SP36), K (Kiserit), the potential land suitability of S1rc was obtained according to the rooting medium (rc), especially texture.  Keywords : Potential of Abaka Banana Plant Land (Musa textilis Nee)